Impact of Selenium on Structural Changes Induced by Hypothyroidism In Adult Male Rat ׳s Testis - Eman Alhealy; Maysoon Alqazzaz; Wahda AL-Nuaimy (University of Mosul, 2021)
Background: The poor solubility of drugs is one of the most important limitations in formulating drugs into suitable dosage forms. In addition, the mechanical properties are the main obstacles in formulating tablet dosage form by direct compression method. Aim of this research: To investigate the possible improvement in mechanical properties, solubility performance, and tableting properties of drug-drug co-crystals of paracetamol and naproxen. Methods: The pre-compression parameters (Angle of repose, Carr’s index, and Hausner’s ratio) of the three paracetamol/naproxen co-crystals were investigated. Moreover, the solubility of the co-crystals was tested as well. In addition, the three paracetamol/naproxen co-crystals were formulated as oral tablets by direct compression method using microcrystalline cellulose and magnesium stearate. The prepared co-crystals were compressed into tablet dosage forms and the dissolution profiles were monitored. Results: The results showed an enhancement in flowability and compressibility of the prepared co-crystals when compared with paracetamol or naproxen alone. The poor tableting properties of prepared paracetamol tablets were very clear and they are in opposite to the co-crystals prepared tablets, which met all the pharmacopeial requirements. The in vitro dissolution study was conducted to compare the dissolution profiles of the prepared co-crystals tablets with marketed paracetamol tablets (Piodol®) and marketed naproxen tablets (Napron®). The dissolution profile of (1 to 2) co-crystal prepared tablets showed a superior dissolution rate with more than 50 % of the paracetamol drug dissolved within the first 5 minutes of dissolution rate. The dissolution study resulted in a better dissolution of the prepared paracetamol/naproxen tablets due to the co-crystal formation. Conclusion: It could be concluded that the prepared paracetamol/naproxen co-crystals represent a promising way for improving flowability and compression properties, enabling the formulation of the co-crystals as oral tablets by direct compression method with a clear enhancement in the dissolution rate.